2018
DOI: 10.1074/jbc.ra117.001569
|View full text |Cite
|
Sign up to set email alerts
|

Sequence diversity of tubulin isotypes in regulation of the mitochondrial voltage-dependent anion channel

Abstract: The microtubule protein tubulin is a heterodimer comprising / subunits, in which each subunit features multiple isotypes in vertebrates. For example, seven -tubulin and eight -tubulin isotypes in the human tubulin gene family vary mostly in the length and primary sequence of the disordered anionic C-terminal tails (CTTs). The biological reason for such sequence diversity remains a topic of vigorous enquiry. Here, we demonstrate that it may be a key feature of tubulin's role in regulation of the permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 69 publications
2
53
1
Order By: Relevance
“…While Ca 2+ stress has been proposed as a primary cause of swollen mitochondria and impaired oxidative phosphorylation in mdx mice [ 5 ], separate observations of altered microtubule networks [ 37 , 38 , 42 ] were also linked to disrupted cytosolic NADPH oxidase-induced ROS and Ca 2+ signaling [ 42 ]. An intriguing possibility of a mitochondrial link to microtubule disorganization emerges when considering the separate discoveries that tubulin components of microtubules can directly bind to VDAC on the outer mitochondrial membrane and decrease its permeability to ADP/ATP cycling [ 10 , 14 , 21 , 29 ]. Considering that pharmacological alterations of microtubule networks changes tubulin-VDAC interactions and ADP-dependent bioenergetics [ 13 ], it seems plausible that the distinct observations of disorganized microtubules and mitochondrial dysfunctions in D2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While Ca 2+ stress has been proposed as a primary cause of swollen mitochondria and impaired oxidative phosphorylation in mdx mice [ 5 ], separate observations of altered microtubule networks [ 37 , 38 , 42 ] were also linked to disrupted cytosolic NADPH oxidase-induced ROS and Ca 2+ signaling [ 42 ]. An intriguing possibility of a mitochondrial link to microtubule disorganization emerges when considering the separate discoveries that tubulin components of microtubules can directly bind to VDAC on the outer mitochondrial membrane and decrease its permeability to ADP/ATP cycling [ 10 , 14 , 21 , 29 ]. Considering that pharmacological alterations of microtubule networks changes tubulin-VDAC interactions and ADP-dependent bioenergetics [ 13 ], it seems plausible that the distinct observations of disorganized microtubules and mitochondrial dysfunctions in D2.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this observation does not rule out the possibility of other tubulin-VDAC interaction combinations. For example, while the CTT tail of α-tubulin has been shown to block the pore of VDAC, there is a greater affinity of the CTT tail on certain β isotypes, particularly βIII and VDAC1 [14]. In addition, it has been suggested that free βII tubulin binds VDAC in muscle-independent of heterodimeric tubulin-such that this free pool may be a distinct regulator of ADP/ATP cycling through VDAC [15].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Rostovsteva and colleagues used a co‐localization assay to identify a likely sensor for the tubulin, which has disordered c‐terminal tails (CTT) that differ between isotypes. Each CTT produces a unique ion current signature based on the distribution of negative charges along the sequence . Several systems have been devised that anchor recognition sites within the pore, such that a portion of the anchor is inside the pore either through a specific biological recognition element (i.e., biotin–streptavidin), or by integrating binding sites to the pore that capture the natural ligand of the protein analyte .…”
Section: Protein Sensingmentioning
confidence: 99%
“…Apoptosis is associated with increased expression of VDAC1 in the outer mitochondrial membrane and oligomerization of VDAC1 monomers to form large channels that allow for release of mitochondrial pro-apoptotic proteins into the cytoplasm where they mediate additional apoptotic events [10,[15][16][17]. Regulation of cell survival signals by VDAC1 occurs through its interactions with proteins of the Bcl-2 family, hexokinase, protein kinases, cytoskeletal proteins (tubulin, α-synuclein, plectin, and desmin), and mitochondrial lipids (cardiolipin and phoshatidylethanolamine) [16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%